Knowledge, attitude, and practice of breast self-examination among female nurses in Aminu Kano teaching hospital, Kano, Nigeria - Yakubu, A. A.; Gadanya, M. A.; Sheshe, A. A. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: The incidence of breast cancer is increasing and the presentation is often late in our environment with poor prognosis. Breast self-examination (BSE) remains an important diagnostic tool for the early detection of breast cancer in a resource-limited community. Nurses being in closer contact with patients should be in the forefront in educating the general public on BSE. Objectives: This study investigates the knowledge, attitude and practice of BSE among female nurses in Aminu Kano Teaching Hospital (AKTH) with regard to the number that practice, method and the frequency of BSE. Materials and Methods: The study is a descriptive cross-sectional study of female nurses employed in AKTH using self-administered questionnaire. Respondents were selected by simple random sampling methods from the register of nursing staff at AKTH. The data collected were on socio-demographic profile, knowledge, attitude and practice of BSE. The relationships between these factors were studied. Results: All the nurses studied are aware about BSE, with 91.2% practicing it. There is appallingly poor knowledge of its timing, frequency and method. Only 45 (41.2%) of the respondents practice BSE monthly, and none of the respondents can accurately describe the exact method of BSE. Conclusion: There is universal awareness of the BSE among nurses, with dismal awareness of its purpose, method, timing, and frequency among the female nursing staff studied. However, there is a lot of enthusiasm to encourage others to do it. Therefore, nurses need to be also further trained and educated about the procedure.